Le sociologue, le climat, les trames vertes et la ville : croisements complexes et féconds - Philippe Boudes (VertigO, 2012)
How to tackle, from a sociological point of view, the existing links between climate, greenways and city ? Despite the non-sociological nature of these items and of their association, the article discusses the possible inputs to address, as a sociologist, these questions. This is, primarily, to take in account sociological fields that are more or less related to these themes : urban sociology, sciences studies and environmental sociology. Each can provide approaches which are likely to contribute to the analysis of the triptych climate, greenways, and city. Furthermore, the article describes an aspect of the research approach used in the program called Climate Change and Urban Greenways (CCTV). A scientometric perspective has first validated the growing links between climate and greenways within the scientific literature. A transversal qualitative analysis then details the principles of these links through three dimensions : the first is about political and sensible forms of these links, the second refers to technical and historical categories of climate/greenways relationship, the third regards the production of data and existing projections.